Implementation of Situation, Background, Assessment, and Recommendation (SBAR) Format During Handover in the Udayana University Hospital - Komang Menik Sri Krisnawati; Ni Putu Emy Darma Yanti; Indah Mei Rahajeng (KHD-Production, 2023)
Effective communication within the hospital environment can significantly improve practice safety in health services, especially during the handover process. Handover is a transfer of information during the shift transition. Numerous studies have presented evidence of the Situation, Background, Assessment, and Recommendation (SBAR) format in enhancing effective communication during handovers. Here, we aimed to explore SBAR communication during handovers in a public hospital in Bali. This quantitative descriptive study applied a cross-sectional approach and employed 20 participants who were selected using a total sampling technique. A questionnaire was enrolled to collect participants’ demography characteristics and the handover process. The majority of participants were female (90%), with a mean age of 28 years, a working duration <3 years (55%), and registered nurses (45%). SBAR format was effectively delivered during the handovers (95%), especially among female participants (85%), aged 29 years old (20%), participants with less than <3 years of working experience (55%), and registered nurses (40%). SBAR format assists a clear, complete, well-directed, and concise organization of clinical information during the handover process. According to the model care, we only found one team member (5%) with ineffective SBAR communication. Ninety-five percent of the participants had performed proper SBAR handovers. We assumed that model of care may associate with SBAR handovers skill.